Rendering slow ecological crisis in a popular medium: Hyperobjects and Sámi resistance in the Swedish-French TV series Midnight Sun - Mrozewicz, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article examines the ways in which the slowly evolving and invisible processes of the ongoing ecological crisis can be represented in the format of a contemporary serial television drama. The author argues that despite heavy reliance on spectacular and captivating character-born plots, the long-form storytelling of new television narratives can be well suited to representing the complex and unspectacular temporalities of the ecological crisis. With the Swedish-French Arctic noir TV series Midnight Sun as a case study, the analysis shows how a highly spectacular criminal plot is developed to reveal the invisible temporal action and nonhuman agency of a special kind of waste paradigmatic of the era of the Anthropocene, defined by Timothy Morton as a hyperobject (2013). This idea is established in Midnight Sun not only by placing radioactive waste at the center of the narrative but also by gradually foregrounding its nonhuman agency behind the events. The aim of the analysis is to demonstrate that by both using and reimagining the conventions of the television crime drama (Arctic noir), Midnight Sun translates into quotidian terms the unspectacular and long-term aspects of human-induced ecological destruction, which surpass the individual human scale and evade our cognition. An important strategy adopted in Midnight Sun is bringing together two levels of criticism: ecocritical and postcolonial. The slow ecological violence (R. Nixon, 2011) and nuclear colonialism (G. Schwab, 2020) exerted by the powerful against regions and people who are globally less visible are depicted as a continuation of the history of colonization, and more specifically, the systemic and longstanding ill-treatment of the indigenous Sámi people in Sweden.